One-step electrodeposition of NixFe3−xO4/Ni hybrid nanosheet arrays as highly active and robust electrocatalysts for the oxygen evolution reaction. Issue 5 (18th February 2020) - Li, Dongjie; Liu, Suqin; Ye, Guanying; Zhu, Weiwei; Zhao, Kuangmin; Luo, Meng; He, Zhen
Abstract : Ni x Fe3− x O4 /Ni hybrid nanosheet arrays have been directly fabricated on different substrates via template-free and annealing-free one-step electrodeposition, which show excellent catalytic performance for the oxygen evolution reaction. Abstract : Non-precious transition metal oxide-based materials have shown a promising prospect as electrocatalysts for the oxygen evolution reaction (OER). Herein, we report a template-free and annealing-free one-step electrodeposition approach for the in situ fabrication of composition- and morphology-controllable Ni x Fe3− x O4 /Ni hybrid and Ni x Fe3− x O4 nanosheet arrays (NSAs) on different conducting substrates as highly active and robust oxygen-evolving electrocatalysts. The optimal Ni x Fe3− x O4 /Ni hybrid NSA electrodeposited on nickel foam requires low overpotentials of only 218 and 262 mV to deliver OER current densities of 10 and 100 mA cm −2, respectively, with a small Tafel slope of 45 mV dec −1, which are the best among the reported Ni–Fe oxide-based OER electrocatalysts. The Ni x Fe3− x O4 /Ni hybrid NSA also exhibits robust stability under the OER conditions, showing no decline in the catalytic activity after a continuous oxygen-evolving test conducted at current densities ranging from 10 to 500 mA cm −2 for a total of 220 h. The excellent electrocatalytic OER performance of the electrodeposited Ni x Fe3− x O4 /Ni hybrid NSA could be attributed to its vertically aligned nanosheet morphology providing a large electrochemically active surface area, better matched Fermi energy of Ni x Fe3− x O4 with the O2 production potential and faster electron transfer due to proper Ni incorporation, and low interfacial resistance and robust contact between the Ni x Fe3− x O4 /Ni hybrid and the substrate due to in situ electrodeposition. This work provides a facile (around 3 min of electrodeposition) and low-cost synthesis strategy that could be applicable for the fabrication of nanostructures of various metal oxides or metal oxide/metal hybrids for different applications.